Structural Strength and Behaviour of Cylindrical Steel Sheet Roofing - Islam, S. M. Zahurul (2005)
The roof does not only protect the building and its occupants from the effects of weather, but it is also an architectural feature that gives the building a desired appearance. Profiled steel sheet zincalume is normally used in roof as covering materials, without any attention paid to its struchiral capability as a self-supporting medium. A self-supporting roofing element is a new; where profiled sheeting roof could run continuous lengths of roof spans without internal support. This roofing system saves material and construction cost by avoiding internal support. The aim of this research work is to study the possibility of using profiled steel sheet as self-supporting roofing elements for affordable housing. An analytical investigation using the finite element method was carried out on the structural strength and behavior of different types of self-supporting roofing elements. Five laboratory tests using 3 m spans, 0.42 mm thickness and different crown heights of 1.5, 1.0, 0.50, 0.25 and 0.125 m specimens were conducted for assessing the structural strength and behavior of roofing elements. Analytical study was camed out on the effect of shape, size, materials and support condition on the structural behaviour of the selected roofing element. The analytical investigation was extended for longer spans to explore the feasibility of using of profiled steel sheet as a self supporting roofing system in housing construction. In the analytical work, finite element models were generated and analyzed by using LUSAS software. The analytical study for the roofing elements showed that parabolic profiled roofing element with crown height 116 of span length was more efficient than others as a self-supporting element. The proposed self-supporting roofing element satisfied geometrical, buckling and material stability. Deflection was found to be the limiting criteria in design for self-supporting roofing element using profiled steel sheet. The presence of corrugation in the steel roofing element resulted in a significant improvement on the roofs structural performance compared to flat sheet element. Good agreement was found between the results from finite element analysis and those obtained experimentally. The FEM models predicted with a reasonable degree of accuracy the structural behavior of different types of roofing elements. It was observed that a parabolic shape roofing element with an optimum crown height could be used as a self- supporting roofing element for about 4 m and 8 m span lengths using 0.42 mm and 1.25 mm thick profiled steel sheet. On the basis of this investigation, parabolic self-supporting roofing elements using profiled steel sheet with optimum crown height could be used in housing construction.